HEMATOLOGICAL AND BIOCHEMICAL FINDINGS AMONG JORDANIAN PATIENT WITH END STAGE RENAL DISEASE - Khasawnah, Nadia; Abu Abeeleh, Jaafar Abd Alrahman (European Scientific Journal, ESJ, 2015)
Chronic renal failure is a continuous decreased loss of renal function which leads to long term renal treatment including renal replacement therapy. One of the renal therapeutic options is renal haemodialysis, which acts in removing body’s waste products, including creatinine, urea and excess water. The present study was conducted to study the frequency of some hematological and chemical parameters among patients with chronic kidney disease at Royal Medical City Clinics. Study methodology implied withdrawing blood samples from study participants to carry out the following hematological and chemical parameters: hemoglobin, hematocrit, mcv, bun, creatinine, phosphorous, calcium, albumin, sodium, and potassium. Study findings showed that patients were anemic (hemoglobin 8.99). Chemical parameters indicated that renal dialysis was not able to effectively maintain chemical constituents of the body. Taken together, the current renal dialysis regimens need to be revised in terms of duration and frequency.